Anmeldelser - Møller Sørensen, Søren (Danish Yearbook of Musicology, 2012)
Review of: Laura Lohman: Umm Kulthum. Artistic Agency and the Shaping of an Arab Legend, 1967–2007. Middletown: Wesleyan University Press, 2010-